2015
DOI: 10.1016/j.chembiol.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Converting a Staphylococcus aureus Toxin into Effective Cyclic Pseudopeptide Antibiotics

Abstract: Staphylococcus aureus produces peptide toxins that it uses to respond to environmental cues. We previously characterized PepA1, a peptide toxin from S. aureus, that induces lytic cell death of both bacterial and host cells. That led us to suggest that PepA1 has an antibacterial activity. Here, we demonstrate that exogenously provided PepA1 has activity against both Gram-positive and Gram-negative bacteria. We also see that PepA1 is significantly hemolytic, thus limiting its use as an antibacterial agent. To ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…In addition, the toxins have to be effectively delivered to habitats of pathogenic bacteria in the patient’s body without deleterious effects on the human cells or normal commensal organisms. The type I toxin PepA1 from S. aureus is a 30-residue hydrophobic peptide that can cause membrane lysis of both bacterial cells and human erythrocytes [190,191]. This toxin was sequentially and chemically optimized to enhance the antibacterial activity and reduce the hemolytic side effect [191].…”
Section: Exploitation Of Ta Systems For the Development Of Novel Amentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the toxins have to be effectively delivered to habitats of pathogenic bacteria in the patient’s body without deleterious effects on the human cells or normal commensal organisms. The type I toxin PepA1 from S. aureus is a 30-residue hydrophobic peptide that can cause membrane lysis of both bacterial cells and human erythrocytes [190,191]. This toxin was sequentially and chemically optimized to enhance the antibacterial activity and reduce the hemolytic side effect [191].…”
Section: Exploitation Of Ta Systems For the Development Of Novel Amentioning
confidence: 99%
“…The type I toxin PepA1 from S. aureus is a 30-residue hydrophobic peptide that can cause membrane lysis of both bacterial cells and human erythrocytes [190,191]. This toxin was sequentially and chemically optimized to enhance the antibacterial activity and reduce the hemolytic side effect [191]. The mechanism of action of PepA1 derivatives can be explained by their structural property such as linear, helical, and cyclic conformations [191].…”
Section: Exploitation Of Ta Systems For the Development Of Novel Amentioning
confidence: 99%
See 1 more Smart Citation
“…First, we developed strategies to synthesize large series of aza‐β 3 ‐amino acids bearing proteogenic or nonproteogenic side chains suitable for straightforward solid‐phase peptide synthesis . Then, we showed that peptides containing aza‐β 3 ‐amino acids can exert various biological activities and we synthesized highly stable AMP mimics with enhanced antimicrobial activities …”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45][46] Then, we showedt hat peptides containing azab 3 -amino acids can exert various biological activities [47][48][49] and we synthesized highly stable AMP mimics with enhanced antimicrobial activities. [50][51][52] The large variety of availables ide chains allowed us to design various aza-b 3 -peptidomimetic sequences, while the abiotic moieties confer resistance against proteolytic degradation. Indeed,w hen incorporated into al inear peptide, aza-b 3amino acids are knownt oe nhance the resistance of the pseudopeptide to enzymatic degradation,a nd we showed that cyclic pseudopeptides combine high metabolic stability with a long half-life.…”
Section: Introductionmentioning
confidence: 99%